In vitro and in silico Anti-diabetes mechanism of phytochemicals from Curculigo pilosa and its pharmacokinetic profiling via α-amylase inhibition - Damilola A. Omoboyowa; Temitope C. Aribigbola; Simbo T. Akinsulure; Damilola S. Bodun; Ezekiel A. Olugbogi; Ebenezer A. Oni (Aspects of Molecular Medicine)
Diabetes mellitus is characterized by elevated blood glucose resulting from carbohydrate metabolism via glucose metabolizing enzymes such as α-amylase. Curculigo pilosa is traditionally used as herbal medication as anti-diabetes therapy but its mechanism of action is yet to be explored. This study investigates α-amylase inhibitory potential of C. pilosa using in vitro and in silico approaches. The ethylacetate, n-butanol and methanol extracts of C. pilosa were subjected to in vitro α-amylase inhibitory assay, followed by identification of the bioactive compounds from the most potent extract using HPLC. Integrated computational analyses were performed on ten (10) active compounds against α-amylase using Maestro Schrodinger (v2). The results of the in vitro α–amylase assay revealed n-butanol extract as the potent extract with IC50 of 132.70 μg/mL, although the standard drug (acarbose IC50 = 128.70 μg/mL) inhibits α-amylase better than the extracts. The HPLC result revealed the presence of ten (10) active compounds. Acarbose was observed to possess better binding affinity (−11.502 kcal/mol) than all the compounds but curculigoside was the hit compound with binding affinity of −8.797 kcal/mol. Some of the compounds showed appreciable inhibitory pIC50 and fitness scores comparable to the standard drug. The pharmacokinetic profile revealed that none of the compounds violated more than one Lipinski's rule of five while the standard drug (acarbose) violated three (3) of the rules. The root mean square deviation shows reasonable level of stability within the simulation period for both curculigoside and acarbose. The result of in silico study showed significant inhibitory potential of the active compounds against α-amylase which was consistent with the in vitro inhibition of α amylase by the plant extract suggesting this as the possible mechanism of antidiabetes action of C. pilosa.